Crystal structure of a new Mo10Ni3C3B phase. (February 2020) - Vershinina, T.N.; Boev, A.O.; Ivanov, M.B.
Abstract: A new Mo 10 Ni 3 C 3 B phase was synthesized during the liquid phase sintering of cermet Mo 2 NiB 2 –Ni doped with carbon. The crystal structure of this phase has been determined by X-ray diffraction analysis and density functional theory calculations. The structure refinement indicates that a new phase has space group P6 3 /mmc (Pearson symbol hP34) and lattice parameters a = 7.8089 Å, c = 7.8712 Å. Atomic coordinates of all elements are determined. Graphical abstract: Image 1 Highlights: Formation of a new phase during liquid phase reactive sintering of Mo2 NiB2 –Ni cermet doped with carbon is observed. Crystal structure of new phase was determined. The equilibrium configuration according to density functional theory method corresponds to Mo10 Ni3 C3 B phase.